Vitamin C in Health and Disease: Its Role in the Metabolism of Cells and Redox State in the Brain - Figueroa-Méndez, Rodrigo; Rivas-Arancibia, Selva (Frontiers in Physiology, 2015)
Ever since Linus Pauling published his studies, the effects of vitamin C have been surrounded by contradictory results. This may be because its effects depend on a number of factors such as the redox state of the body, the dose used, and also on the tissue metabolism. This review deals with vitamin C pharmacokinetics and its participation in neurophysiological processes, as well as its role in the maintenance of redox balance. The distribution and the concentration of vitamin C in the organs depend on the ascorbate requirements of each and on the tissue distribution of sodium-dependent vitamin C transporter 1 and 2 (SVCT1 and SVCT2). This determines the specific distribution pattern of vitamin C in the body. Vitamin C is involved in the physiology of the nervous system, including the support and the structure of the neurons, the processes of differentiation, maturation and neuronal survival; the synthesis of catecholamine, and the modulation of neurotransmission. This antioxidant interacts with self-recycling mechanisms, including its participation in the endogenous antioxidant system. We conclude that the pharmacokinetic properties of ascorbate are related to the redox state and its functions and effects in tissues.